Effectiveness of a lean simulation training: challenges, measures and recommendations. Issue 6 (24th April 2021) - Adam, Martin; Hofbauer, Maximilian; Stehling, Marius
Abstract: Teaching adults in Lean Management faces certain challenges. One well-known concept to deal with them is activity-based learning like it is provided by learning factories. This paper explores the main challenges and its influence as well as learning methods in the context of a Lean Learning Lab from the system's perspective. The effectiveness of the training is evaluated by the overall impression, by how easy it is to understand the theory and whether the participants dared to transfer the content into their working environment. The study was conducted in the Lean Lab of the University of Applied Sciences in Kufstein with a large sample of participants from different local companies. The study showed that participants had difficulties with understanding the benefits of Lean Management, its theory and the terminology. This was significantly influenced by the hierarchy of job and the participant's level of education. Of major help during the training was the change between theory and practice. In addition, the 'do-it yourself' approach was supportive, too. Here again, the job position significantly determined the choice of support. When it comes to the effectiveness of the training with regard to understandability and transfer, not all of the Lean tools received equally good ratings. Transfer to real life was significantly influenced by how understandable the Lean tools were and how easy it was to implement them in the Lean Lab. This study provides a system model of the training situation with statistically proven insights into how to organise a Lean Basic Training for adults in order to provide an effective training for them.